Analisis Praktek Keperawatan Medikal Bedah dengan Pendekatan Teori Adaptasi Roy pada Pasien Gangguan Persyarafan di RSUPN dr. Cipto Mangunkusumo Jakarta - Pujiarto Pujiarto (Politeknik Kesehatan Tanjung Karang, 2017)
Methods that used in Medical surgical nursing practice were the case study design. It was done by implement nursing care in patients with impaired neurological using Roy's adaptation model. Cerebral tissue perfusion disturbances, impaired physical mobility, and self-care deficit were problem of nursing that commonly happen in patients with neurological disorders. Nursing interventions were needed to aim to address those nursing issues. Application of the theory adaptation Roy were very appropriate in patients with impaired neurology, because it is one theory that is dynamic and focused on adaptability of patients and included theory easily applied in the implementation of nursing care. Roy asserts that the individual is a biopsychosocial beings as a unified whole that have the coping mechanisms to environmental changes in order to achieve an adaptive condition.